The gift of love [videorecording (DVD)] - Chaffey, Don, 1917-1990; Osmond, Marie, 1959-; Bottoms, Timothy, 1949-; Woods, James, 1947-; Lockhart, June, 1925-; Wayne, David, 1914-1995; Henry, O., 1862-1910 (Monterey Video, 2003)
Played against the tapestry of early 1900s New York City, this touching tale of selflessness brings O. Henry's Christmas valentine lovingly to the screen. A beautiful and wealthy orphan (Marie Osmond) is dutifully resigned to an arranged-for marriage to a man of "socially acceptable class" (James Woods), when her heart is captured by a young Swiss immigrant (Timothy Bottoms). Within her heart she wages the struggle to fulfill her relative's expectations, and yet to find for herself that most precious of all joys, "The Gift of Love."--Container.